Revisiting the Balkan Crisis: AUn Question; The European Connection and the Us Solution - Jackson Nyamuya margoto (Fakultas Hukum Universitas Islam Indonesia, 2002)
The more fundamental decision for the States of the international community, however, was whether to make the concessions necessary to create an effective internationalmechanism against the background of States insisting upon preserving the totality of their sovereign prerogatives, if such aview had held sway, no effective international criminal tribunal could have been created.